Pengaruh Penggunaan Media Sosial TikTok terhadap Personal Branding Mahasiswa Penyedia Jasa Rias Wajah - Dinda Ayu Puspita; Maria Krisnawati (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
The purpose of this study is to examine the influence of TikTok social media on the personal branding of makeup service students. With its interactive short video format, TikTok allows students to showcase their talents and reach a wider audience. This study explains how TikTok usage influences personal branding and offers practical advice for individuals, creators, and especially makeup service students. Google Form was used to conduct an online survey using a non-experimental quantitative methodology. There were 65 students from the class of 2022 in the Beauty Education Study Program, Semarang State University, who became the sample. In this study, the data results met the conditions indicated by the validity test, reliability, classical assumptions, simple linear regression, t-test, and determination test. The t-test results showed that the TikTok social media usage variable (X) had a t-value of 8.182 and a significance value of 0.000. Because this significance value is less than 0.05 (0.000 < 0.05), it can be concluded that H0 is rejected and Ha is accepted. These findings indicate that TikTok social media usage contributes to the development of personal branding and plays a role in supporting audience interaction and increasing public perceptions of trust. The platform also provides a relevant platform for student makeup artists to build visibility and document their portfolios digitally.